PEMANFAATAN IKAN RED DEVILCICHLID (Amphilophus labiatus, Günther 1864) DARI DANAU SENTANI, JAYAPURA, PAPUA - Henderite L. Ohee; I Made Budi (JURNAL PENGABDIAN PAPUA, 2021)
Lake Sentani is the main freshwater fish source in Jayapura. It also supports livelihood of local people as fisherman. Red devil cichlid (Amphilophus labiatus, Günther 1864) is one of introduced species in the lake. It is the most abundance fish in the lake. In the program, we used the fish as the base ingredient of meatballs. Aim of the activity is to increase community knowledge on local food processing and to improve nutrition statues of local people in Ayapo Village, East Sentani District, Jayapura. The program was conducted in June 28, 2018 in Biology Department of Mathematics and Natural Sciences Faculty, Cenderawasih University. The program was held in collaboration with CV Budi Mulya Asih in Waena and Woman Fellowship Group of local church in Ayapo Village. Red devil cichlid was cleaned and the head cut to be cooked using high pressure. The cooked meat then being grind and mix with sago flour and the other herbs and spices. The ratio is 20-30% sago flour mix with 70-80% fish. After the meatballs batter ready, it can be formed into desired form and boil in hot water until the meatballs floating. After cooling the meatballs, it is then ready to be served or packed. Unfortunately, the first red devil cichlid of Lake Sentani meatballs were not turned out as delicious as expected. Therefore, it is expected that next experiment will produce delicious red devil cichlid meatball. Keywords: lake sentani, Jayapura, freshwater, fish, red devil cichlid